Technical scheme of the unified account authentication service for operators - Maowen GUO; Rong ZHANG; Yanqing LU; Yan LI (Dianxin kexue)
Aiming at the pain point of current internet applications,on the basis of analyzing the key factors that should be considered in the development of unified account authentication service,a technical scheme of unified account authentication service based on mobile phone number was put forward,including the overall architecture of the system,the application interface scene,and the implementation of differentiated authentication.Then,the related ideas about the operators’ unified account authentication service interconnection were analyzed.Finally,the prospect of the operators to develop unified account authentication service was also discussed.